Analysis Prediction Model Determinants of Chronic Energy Deficiency (CED) Pregnant Women in Jambi City - Lanita, Usi; Asparian, Asparian; Astuti Siregar, Sri (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: One of the nutritional problems in pregnant women that is important to overcome is Chronic Energy Deficiency (CED).  Objective: This study aims to determine the prediction model of the determinants of the causes of CED in pregnant women. Method: This type of quantitative research with a cross-sectional design on 98 pregnant women in Jambi City in 2024, sampling was purposive. Data analysis used Chi Square test and Logistic Regression. Result and Discussion: There is a significant relationship between income (0.008), Hb levels (0.009), provision of additional food (0.008), knowledge (0.003), attitude (0.032), the role of health workers (0.043) with the incidence of CED in pregnant women. There is no relationship between age (0.377), education (0.294), occupation (0.306), infectious diseases (0.117), and non-infectious (0.206) with the incidence of CED in pregnant women. The dominant factor is the knowledge of pregnant women. Conclusions: The prediction model for the incidence of CED in pregnant women is income, Hb levels, provision of additional food, knowledge, and the role of health workers. It is recommended that the Health Service and Health Centers always provide education to improve the knowledge of pregnant women about the prevention and treatment of CED.